Kajian Media Terhadap Pemberitaan Proses Legislasi Undang-Undang Cipta Kerja - Buchori, Masad Masrur (Unitri Press, 2021)
The agenda setting of Mass Media in Indonesia, which tends to be pro towards the presence of the Job Creation Law, is considered not an actual articulation of the public interest (receiver) which it should represent. Theory, research, and even digital surveys involving the mass media as news subjects (channels) assess that the mass media are trapped in insignificant, normative news and do not accommodate counter opinions in an objective and balanced manner. The public then uses new media, especially social media, to mobilize a movement against the Job Creation Law, or to broadly mobilize pro-democracy forces through this movement. Although social media is not a mass media that applies measurable journalistic principles, social media offers digitization, convergence, interactivity, and development of network, which are considered more effective in articulating the true public interest in political communication towards the government as the messenger (sender). Keywords: government; job creation law; mass media; social media